SOCIAL-PHILOSOPHICAL FOUNDATIONS OF DEVELOPING A CULTURE OF INTERNATIONAL TOLERANCE (Modern American Journal of Social Sciences and Humanities, 2026)
In the article, the peaceful living of the representatives of the nation in one country, the striving to develop the principles of universal tolerance, are philosophically based on the characteristics of the new century. However, according to the law of uneven development of culture, due to the fact that the culture factor is not sufficiently manifested in some societies, various destructive actions against the existing political power arose in them, and their effects on the stability and development of other nations and states were also analyzed.